Penerapan Asuransi di Kehidupan Masyarakat Dalam Lembaga Keuangan Bukan Bank - Gandhi Sulaiman Sitompul; Zainarti Zainarti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This research explores an in-depth understanding of how society responds to insurance policy analysis in non-bank financial institutions through a phenomenological approach. The findings show that limited financial literacy is the main challenge in understanding the complexity of insurance products outside of banking. The influence of personal experience, cultural values, and risk perceptions also shape people's perceptions of the value of insurance. Additionally, variations in participation levels and decision-making patterns were also revealed, weakening the understanding of risk levels. These financial literacy challenges cause chaos and confusion, hindering public participation in insurance products at non-bank financial institutions. Efforts to improve financial literacy and increase understanding of insurance claims are crucial to stimulate optimal community participation. The application of insurance remains relevant in helping people overcome financial problems due to unexpected events, building trust, and creating economic stability in the context of non-bank financial institutions.